Screw view model of navigation in posterior corrective surgery for adolescent idiopathic scoliosis: A case report and technique note. Issue 12 (March 2019) - Yu, Tong; Yang, Lili; Zheng, Shuang; Qu, Yang; Zhang, Xiwen; Kang, Mingyang; Dong, Rongpeng; Zhao, Jianwu
Abstract: Rationale: The purpose of this study is to introduce the application of screw view model of navigation (SVMN) for adolescent idiopathic scoliosis (AIS). It is a challenge to insert pedicle screw into the vertebral body of scoliosis, and the misplaced screw may lead to neurovascular injury. In order to minimize surgical complications, we used a novel method of SVMN technology to facilitate pedicle screw insertion. Patient concerns: Her mother brought her to our outpatient department upon noticing the girl's different heights of shoulders and unbalance of the trunk. Diagnoses: She was diagnosed with AIS and syringomyelia. Interventions: We used an SVMN technology to assist pedicle screw insertion and correction surgery in this 20-year-old patient. Outcomes: This study indicates that the SVMN could obtain a satisfactory surgical effect for AIS. The Cobb angle of segmental scoliosis (T7-L2) was 55° before surgery, and 3.5° after surgery, and the rate of correction was 93.6%. The segmental kyphosis (T7-L1) was 56.8° preoperatively and 32° postoperatively with the rate of correction of 43.6%. The distance between the center sacral vertical line (CSVL) and the C7 plumb line (CPL) was reduced from 56.2 mm to 0.2 mm, and the sagittal imbalance of 35.8 mm was improved to 3.5 mm. In addition, the misplacement of pedicle screws, the volume of blood loss, the operation time, and surgical complications were also recorded. The follow-up duration was 33 months. Lessons: The utilization of SVMN in AIS might reduce the incidence of screw misplacement and avoid neurovascular damage, as well as a satisfactory correction. The application of SVMN for AIS is an efficacious and safe method.